Effect of entomopathogenic nematodes on nymphs of Aeneolamia albofasciata and its persistence in sugarcane soils of Veracruz - Parada Domínguez, Oscar; Alatorre Rosas, Raquel; Guzmán Franco, Ariel Wilbert; Hernández Rosas, Francisco; Rojas Avelizapa, Luz Irene; Ruíz Vera, Víctor Manuel (Revista Mexicana de Ciencias Agrícolas, 2019)
The objective of this study was to evaluate the pathogenicity of nematodes, Heterorhabditis sp. (CPVG13) and Steinernema spp. (CPVC12, CPVC13) on the spittlebug, Aeneolamia albofasciata and determine its persistence in the soil of three sugar mills Potrero, Constancia and Motzorongo, of the state of Veracruz. In the first experiment the pathogenicity of the entomopathogenic nematodes was evaluated in nymphs of spittlebug, A. albofasciata of 3rd and 4th instar, 120 (infective juvenile) JI/nymph were applied on boxes with six cavities, previously covered with filter paper, each cavity contained a grass stolon (Cynodon sp.) and a nymph per cavity. In the second experiment, the persistence of entomopathogenic nematodes (NEPs) in soil was evaluated; the experiment lasted 70 days, with independent weekly evaluations, of 32 experimental units per week. The pathogenicity experiment revealed that both nematodes were able to cross the saliva that protects the nymphs, kill and develop in the corpses producing new progeny of JI. The highest mortality (62.5%) was observed with Heterorhabditis (CPVG13), also producing the highest concentration of JI per nymph (3500JI/nymph). Significant differences were found between the persistence profiles between Heterorhabditis (CPVG13) and Steinernema (CPVC12). A significant effect of the soil on the survival of both nematodes was found. The isolation that persisted most in soil was the Steinernema compared with that of Heterorhabditis (CPVG13). Deepening these studies, will allow to determine the impact of the interaction between spittlebug-NEPs and the soil.